Traumatic asymmetrical bilateral hip dislocation in an adult. Issue 6 (1st November 2001) - Lam, F; Walczak, J; Franklin, A
Abstract : Bilateral hip dislocation occurring as a result of trauma is a rare condition. Simultaneous anterior and posterior traumatic dislocation of both hips is even more unusual. A case is reported of asymmetrical bilateral traumatic hip dislocation without an associated fracture of the pelvis or femur occurring in a young adult with no previous history of hip abnormality or ligamentous laxity. An unusual mechanism for this injury is also described.